2020
DOI: 10.1111/hequ.12297
|View full text |Cite
|
Sign up to set email alerts
|

Navigating managerial and entrepreneurial reforms in research‐intensive universities: A comparison of early career trajectories in Hong Kong and Canada

Abstract: This article conveys the results of a reflexive investigation of the managerial practices and entrepreneurial discourses that shape the academic trajectories of early career scholars. Beginning with the experiences of early career scholars in research-intensive universities in Canada and Hong Kong, the authors explore some of the social and politicaleconomic relations that are reshaping higher education systems across the world. Drawing on experiences navigating university governance, funding and performance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Thus, although recent strategic plan formulation should have prompted significant advances in lecturers' KT engagement, no effective accomplishments have been observed.To explain this imbalance, it is essential to recognize the important role that lecturers play in the university system since they perform the core functions of their organizations. Studies have suggested that KT engagement conflicts with existing institutional management mechanisms (Etomaru et al, 2022), strongly affecting how lecturers perform their work (Nichols & Hayes Tang, 2022). In this research, we assume that this conflict is caused by misalignment between performance management systems (PMSs) and planned KT strategic goals so that aligning universities' PMSs with their strategic plans could be critical to achieve lecturers' engagement.…”
mentioning
confidence: 99%
“…Thus, although recent strategic plan formulation should have prompted significant advances in lecturers' KT engagement, no effective accomplishments have been observed.To explain this imbalance, it is essential to recognize the important role that lecturers play in the university system since they perform the core functions of their organizations. Studies have suggested that KT engagement conflicts with existing institutional management mechanisms (Etomaru et al, 2022), strongly affecting how lecturers perform their work (Nichols & Hayes Tang, 2022). In this research, we assume that this conflict is caused by misalignment between performance management systems (PMSs) and planned KT strategic goals so that aligning universities' PMSs with their strategic plans could be critical to achieve lecturers' engagement.…”
mentioning
confidence: 99%